Bioactive Compounds Isolated from Lignin of Empty Bunch Palm Fiber and Their Effects on in Vitro Rumen Fermentation - M. Prayuwidayati; T. C. Sunarti; . Sumardi; . Subeki; K. G. Wiryawan (Media Peternakan, 2015)
The objective of this experiment was to study the effects of bioactive compounds isolated from purified lignin formacell (PLF) of empty bunch palm fiber as natural antimicrobes and their effects on in vitro rumen fermentation. The first experiment was inhibition test of 11 bioactive compounds isolated from PLF, using disc diffusion method against the growth of Escherichia coli, Salmonella typhimurium, and Staphylococcus aureus. Four of the most potential bioactive compounds were then used in the second experiment, which was an in vitro test using fresh rumen liquid of Ongole grade beef cattle, to study their effects on rumen fermentation. Six treatments with 3 replications were applied in a completely randomized block (CRB) design. The treatments were R0= 0.5 g basal diet; R1= R0 + 0.3 mg Rumensin®; R2= R0 + 0.3 mg syringaldehyde; R3= R0 + 0.3 mg p-hydroxybenzoic acid; R4= R0 + 0.3 mg m-hydroxybenzoic acid; and R5= R0 + 0.3 mg oxybenzene. Isolate fraction of CC-2 (syringaldehyde), CC-3 (m-hydroxybenzoic acid), VLC-5 (oxybenzene), and VLC-9 (p-hydroxybenzoic acid) exhibited antimicrobes activity against all tested bacteria. Other isolated fractions exhibited antimicrobes activity only against 1 or 2 tested bacteria. The use of syringaldehyde, p-hydroxybenzoic acid, m-hydroxybenzoic acid, and oxybenzene improved ammonia concentration, microbial protein synthesis, and nutrients digestibility. Bioactive compounds had no effect on rumen pH but reduced total VFA concentration as well as the estimate of methane production.Key words: bioactive compounds, natural antimicrobes, rumen fermentation